Pengaruh Teknik Self Talk Untuk Meningkatkan Adversity Quotient Pada Remaja (Studi Single Subject Research Terhadap Siswa Penerima Program Afirmasi Pendidikan Menengah Di SMAN 2 Kota Serang) - Ustsani, Firda; Khairun, Deasy Yunika; Conia, Putri Dian Dia (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2024)
Adversity quotient is a person's ability to think, manage and control their actions in cognitive and behavioral aspects, as well as their resilience to challenges and difficulties that enable them to continue to struggle diligently in achieving life goals or success. This research aims to assess the impact of individual counseling services using self-talk techniques in increasing the adversity quotient of students who receive confirmation of secondary education at SMA Negeri 2 Serang City. The research method used is single subject study with an A-B-A research design. The research results show that there is no overlap between the conditions in this study at 0%. Data obtained from the results before and after the intervention showed that the adversity quotient score in the baseline phase A1 was 63, while in the baseline phase A2, the score increased to 90, indicating an increase of 27 points or 43%. Based on the data analysis, it can be concluded that the self-talk technique has proven to be effective in increasing the adversity quotient of students who receive secondary education affirmation at SMA Negeri 2 Serang City.